System and method for dynamic multi-objective optimization of machine selection, integration and utilization - FUNDERBURK, MARK; THERON, JOHN CHRISTOPHER; LIN, KA-HING; DISCENZO, FREDERICK M; SUGARS, MICHAEL EUGENE; BAIER, JOHN J; SUSTAETA, ANGEL; SNYDER, RIC (2010)
The invention provides control systems and methodologies for controlling a process having computer-controlled equipment, which provide for optimized process performance according to one or more performance criteria, such as efficiency, component life expectancy, safety, emissions, noise, vibration, operational cost, or the like. More particularly, the subject invention provides for employing machine diagnostic and/or prognostic information in connection with optimizing an overall business operation over a time horizon.